ANALISIS KEMAMPUAN BERBICARA MELALUI METODE BERCERITA PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS II SD NEGERI KALIBUNTU - Ilah Sarmila; Sastra Wijaya; Siti Rokmanah, Muhammad Zambri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speaking skill is one of the essential language competencies that support the learning success of elementary school students. However, in reality, most second-grade students still face difficulties in expressing ideas coherently, lack self-confidence, and have limited vocabulary use. This study aims to analyze the speaking skills of second-grade students at SD Negeri Kalibuntu through the application of the storytelling method. The research employed a descriptive qualitative approach with second-grade students of SD Negeri Kalibuntu as the subjects. Data were collected through observation, interviews, and documentation, covering several indicators of speaking skills, including fluency, confidence, vocabulary use, expression, intonation, and comprehension of the story. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings revealed that the storytelling method improved students’ speaking skills across all indicators. Students became more fluent in delivering stories, more confident in performing in front of the class, used new vocabulary, and showed more appropriate expressions and intonation. Thus, the storytelling method is proven to be effective in enhancing elementary students’ speaking skills.